Extracervical Approaches to Substernal Thyroid Goiter Resection: A Systematic Review and Meta‐Analysis - Najm S. Khan; Yingting Zhang; Kassie Bollig; Craig A. Bollig (OTO Open, 2024)
Abstract Objective To evaluate the prevalence of extracervical approaches (ECAs) for substernal goiter (SSG) excision. Data Sources Search strategies created in collaboration with a medical librarian were implemented using PubMed, Cochrane, Scopus, Web of Science, and Google Scholar from inception to July 2021. Review Methods Participants included adults ages >18 years undergoing SSG excision. The primary outcome was rate of ECA via sternotomy or thoracotomy. Studies were categorized into the 3 most common distinct definitions: goiter descending below the plane of the thoracic inlet (definition 1), ≥50% of thyroid mass extending below the sternal notch (definition 2), and goiter extending ≥3 cm below the suprasternal notch when the neck is hyperextended (definition 3). Two reviewers independently extracted data for analysis and performed a quality assessment using the Methodological Index for Non‐Randomized Studies criteria. Results Of the 551 studies identified, 69 studies were included for analysis. Definition 1 included 3441 patients from 31 studies; definition 2 included 2957 patients from 26 studies; and definition 3 included 2921 patients from 12 studies. A random‐effect model estimating the pooled prevalence of ECA using definition 1 resulted in prevalence of 6.12% (95% confidence interval: 3.48‐9.34, I2 = 90.72%). Conclusion Extension below the thoracic inlet is the most widely used definition of SSG. Approximately 6% of patients with a SSG undergo an ECA. Patients with SSG undergoing surgery should be counseled on the prevalence, risks, and morbidity of an ECA in the rare occurrence it is needed.